Treatment of fungal pyelonephritis and ureterolithiasis with a subcutaneous ureteral bypass system and systemic antifungal medication in a cat - McQuitty RG (Dove Medical Press, 2018)
Rebecca G McQuitty,1 Erinne M Branter2 1Emergency and Critical Care Department, ACCESS Specialty Animal Hospital, Culver City, CA, USA; 2Interventional Radiology/Endoscopy Department, ACCESS Specialty Animal Hospital, Culver City, CA, USA Purpose: We describe a case of ureteral obstruction and fungal pyelonephritis in a cat. The case was managed successfully with a subcutaneous ureteral bypass (SUB) device and systemic antifungal medication. Case summary: A 9-year-old, male, neutered, domestic shorthair cat was referred for severe azotemia, ureteral obstruction, and sonographically identified progressive pyelectasia of the left kidney. A SUB device was placed. Cytology of the left kidney subsequently identified fungal organisms, and the cat responded clinically to treatment with fluconazole and supportive care. The cat survived for 11 months with intermittent fluconazole treatment. Conclusion: Fungal pyelonephritis should be considered as a possible concurrent diagnosis in cats with ureteral obstruction. The successful clinical outcome in this case suggests that treatment with SUB placement, antifungal medication, and supportive care could be an effective treatment strategy. Keywords: interventional radiology, ureteral obstruction, mycoses, invasive fungal disease, urinary tract infection